Cloning and characterization of the gene for Escherichia coli seryl-tRNA synthetase. - Härtlein, M (1987)
Seryl-tRNA synthetase is the gene product of the serS locus in Escherichia coli. Its gene has been cloned by complementation of a serS temperature sensitive mutant K28 with an E. coli gene bank DNA. The resulting clones overexpress seryl-tRNA synthetase by a factor greater than 50 and more than 6% of the total cellular protein corresponds to the enzyme. The DNA sequence of the complete coding region and the 5'- and 3' untranslated regions was determined. Protein sequence comparison of SerRS with all available aminoacyl-tRNA synthetase sequences revealed some regions of significant homology particularly with the isoleucyl- and phenylalanyl-tRNA synthetases from E. coli.